Environmental impacts of a hydrometallurgical process for electronic waste treatment: A life cycle assessment case study. (1st January 2017) - Iannicelli-Zubiani, Elena Maria; Giani, Martina Irene; Recanati, Francesca; Dotelli, Giovanni; Puricelli, Stefano; Cristiani, Cinzia
Abstract: The recovery of precious metals through hydrometallurgical techniques is one of the most active research areas on recovery of metals from electronic scraps. In this perspective, a pilot plant was designed for the treatment of small WEEE (Waste Electrical and Electronic Equipment) via hydrometallurgy. The process is based on two different leaching steps, in nitric acid and in aqua regia, followed by electrodeposition processes, to mainly recover copper, silver and gold. Two adsorption steps were also carried out to recover nickel and tin. The goal of the present study is to assess the environmental impacts associated with the designed hydrometallurgical treatment of the small WEEE through Life Cycle Assessment (LCA) methodology. The approach considered is cradle-to-gate, i.e., from the collected WEEE entering the collection centre to the secondary metals obtained from the hydrometallurgical treatment. Results obtained by SimaPro software and CML-IA method show that the nitric acid leaching contributes mostly to the impacts of the hydrometallurgical process (from 40% to 80%), followed by the adsorption steps. From an environmental perspective, the latter can still be improved at the design phase by increasing the lifetime of the sorbents. Highlights: A pilot plant was designed for the treatment of small E-waste via hydrometallurgy. Life Cycle Assessment was performed to analyse the associated environmental impacts. Nitric acid leaching contributes mostly to the impacts (from 40% to 80%). Environmental performances could be improved by optimizing the adsorption step.